ANALISIS KEMAMPUAN MENYIMAK CERITA PENDEK SISWA KELAS II SDN CINDEREJO SURAKARTA - Susilowati, Retno (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2023)
Listening is a daily activity that will be carried out by humans. Listening is soimportant for humans because humans cannot carry out verbal communicationactivities if they do not carry out listening activities. This research was motivated byproblems in listening skills in class II elementary school students. This research is aqualitative descriptive study conducted in an elementary school in Surakarta, Central Javawith a total of 12 students as subjects. This study aims to determine the ability tolisten to short stories, the factors that cause difficulties in listening to short stories,and find out the solutions to improve the ability to listen to short stories in class IIelementary school students. The instruments used in this study were tests onstudents, student interviews, and interviews with class II teachers. The results ofthis study indicate that the ability to listen to short stories for grade II elementaryschool students varies. Judging from the results of the study of 12 students, 3students were categorized as good, 7 students were categorized as sufficient, and2 students were categorized as lacking. Factors that influence the ability to listen tostories are psychological factors, environmental factors, and motivational factors.Efforts that can be made to improve the ability to listen to students' stories are usinganimated films as learning media, doing ice breaking before learning begins, andarranging classrooms in such a way as to create a conducive classroom, as well asallowing students to get equal opportunities to listen and be listened to.Keywords: Listening ability, children's literature, elementary school